THE EFFECT OF EDUCATIONAL LEAFLET USING BLOOD ADDED TABLETS ON THE KNOWLEDGE LEVEL OF PREGNANT MOTHER PATIENTS WITH ANEMIA AT PUSKESMAS 1 JEMBRANA - Dewi, I Gusti Ayu Diah Candra; Sutema, Ida Ayu Manik Partha; Suasnawa, I Gede (Journal Pharmaceutical Science and Application, 2022)
Background: Anemia in pregnancy is a condition where the hemoglobin (Hb) level is less than 11gr/dl in women who are pregnant. Providing education through leaflets to pregnant women is expected to help prevent anemia during pregnancy. Objective: The purpose of this study was to determine the effect of providing education on the use of blood supplement knowledge on the level of knowledge of pregnant women with anemia at Puskesmas I Jembrana in 2022. Methods: The research design used in this study was a quantitative study with a pre-experimental design approach of Groups Pretest-Posttest. The sampling technique used was total sampling with 67 pregnant women with anemia. Results:   The results of this study revealed that there was an effect of leaflet education on the use of blood-added tablets on the knowledge level of pregnant women with anemia at Puskesmas 1 Jembrana with a p-value of 0.000 < (0.05) and a mean difference in the pretest and posttest values ??of 5.43. Conclusion: There is a significant effect between the level of knowledge about the use of blood steadfast tablets and the incidence of anemia in pregnant women. It is hoped that the public, especially pregnant women, will pay more attention to their condition and always consult health workers regarding the use of blood-added tablets. Keywords: Anemia; Leaflet; Knowledge